Art Music by Caribbean Composers: Introduction to Volume 1: Bahamas, Guadeloupe, Haiti, Jamaica, & U.S. Virgin Islands - Gangelhoff, Christine; LeGrand, Cathleen (International Journal of Bahamian Studies, 2011)
The goal of this project, now in its first volume, is to identify and list all available information on the art-music tradition of the Caribbean region - starting with the countries of Bahamas, Guadeloupe, Haiti, Jamaica and the US Virgin Islands. It will, ultimately, form a comprehensive document of value to musicians, ethnomusicologists, historians, researchers, educators and students.